Peningkatkan Keterampilan Berbicara Menggunakan Two Stay Two Stray dalam Pembelajaran Bahasa Indonesia pada Siswa Kelas V SD Inpres Bontomanai (International Forum of Researchers and Lecturers, 2024)
. This study reveals the application of the learning model using two stay two stray by determining the main problem that becomes the focus of the study, namely the low ability of students to express opinions about the material about the intristic story through this class action research in general to improve speaking skills learning at SD Inpress Bontomanai and specifically aims to improve students' speaking skills in class V students of SD Inpress Bontomanai Tamalate District Makassar City. The purpose of this study was to determine the improvement of speaking skills using TWO STAY TWO STRAY in Indonesian Language Learning for Class V Students of SD Inpres Bontomanai.Implementation of research using Speaking Test. The type of research used, namely classroom action research (PTK) which is designed through two cycles. Each cycle lasted for 4 (four) meetings. The subjects in this study were fifth grade students of SD Inpress Bontomanai, Tamalate District, Makassar City, totaling 24 students consisting of 8 boys and 16 girls. Based on the observation data, it can be seen that students' speaking skills through Two Stay Two Stray learning have reached high criteria with an acquisition score of 90. Meanwhile, the results of the student speaking skills test in cycle II show that the average value of speaking skills of grade V students is 83.33%. The test scores of students' speaking skills in cycle II consisted of 4 students who were not yet complete (16.66%), while students who had reached learning completeness were 20 students (83.33%).